Evaluasi Program Hipertensi di Pelayanan Kesehatan Puskesmas Blang Bintang Kabupaten Aceh Besar - Nana Wildana; Muhammad Ghifari Karsa; Marhamah Marhamah; Farrah Fahdhienie; Faisal Abdurahman (Pelantar Press, 2025)
Hypertension is one of the global health problems that contributes to high morbidity and mortality. A hypertension evaluation program in health services is needed to assess the effectiveness of interventions that have been carried out and to improve the quality of health services. The purpose of this study was to evaluate the implementation of the Chronic Disease Management Program (Prolanis), especially for hypertension patients at the Blang Bintang Community Health Center, Aceh Besar Regency, during the period 2022–2024. Evaluation of the hypertension control program at the Blang Bintang Community Health Center through observation of annual report data and direct interviews with the person in charge of PTM at the Blang Bintang Community Health Center regarding aspects of planning, implementation, involvement of health workers and program achievement results, data collection techniques using secondary data, namely the performance report of the Blang Bintang Community Health Center for the period 2022–2024. The Hypertension Prolanis Program at the Blang Bintang Community Health Center for the period 2022–2024 has shown progress in the implementation of community-based services. The increase in the number of human resources, budget, and logistics has provided a strong foundation in carrying out educational and preventive activities for hypertension patients. Routine exercise, regular medication distribution, and group education are key pillars of this program's success. The study concluded that the program has been effective in the short term, but its long-term success depends heavily on the system's ability to measure, monitor, and continuously improve its implementation